Rancang Bangun Augmented Reality Book Meneladani Kisah Umar bin Khattab - Haiva.J.; Chintiya Larashati (ANWARUL, 2026)
Although augmented reality-based character education media have been widely developed, the integration of the exemplary story of Umar bin Khattab, motion graphics, storybooks, and parental assistance into a single learning medium remains limited. This study aimed to design and evaluate the Augmented Reality Book Meneladani Kisah Umar bin Khattab as a character education medium for children aged 5–12 years. The study employed a mixed-methods approach with descriptive analysis and a 4D research and development design comprising the define, design, develop, and disseminate stages. The study participants consisted of 20 respondents selected through purposive sampling. Data were collected through questionnaires, open-ended questions, a literature review, expert evaluation, alpha testing, and beta testing and were subsequently analyzed using quantitative descriptive and thematic analyses. The results showed that a printed book, two-dimensional illustrations, motion graphics, voice narration, and visual markers were successfully integrated through Artivive. Most users assigned scores of 4–5 to the attractiveness of the illustrations, ease of scanning, and comprehensibility of the story, while the delivery of honesty values and media feasibility predominantly received a score of 5. These findings indicate that the developed media are feasible for supporting character education through interactive multimedia and emphasize the importance of parental assistance in helping children understand exemplary values. This study contributes to the development of character education media that integrate storybooks and augmented reality technology, while future research should involve a larger sample, employ experimental testing, optimize file sizes, and develop an offline mode.